Impact of garden cress supplemented biscuits on nutritional profile of malnourished and anemic school children (seven–nine years). Issue 4 (10th July 2017) - Jain, Tanu; Grover, Kiran; Gill, Navjot Kaur
Abstract : Purpose: This paper aims to evaluate the impact of garden cress supplemented biscuits on the nutritional status of malnourished children. Design/methodology/approach: For the present study, 60 underweight and anemic seven-nine-year-old school children were selected according to the World Health Organization (WHO) classification and divided into two groups, i.e. experimental (30) and control (30). Biscuits (60 g) developed using roasted garden cress seeds were supplemented to the experimental group, while biscuits without garden cress seeds were provided to control group for a period of three months and impact was observed in terms of improvement in nutritional status of subjects before and after the supplementation. Findings: The food and nutrient intake increased with increased percent nutrient adequacy and sharp increase ( p ≤ 0.05) was noticed in cereal, fat and sugar after supplementation. Average height, weight, body mass index and mid-upper arm circumference increased, with 3.56 and 0.87 per cent gain in weight and height ( p ≤ 0.05) respectively. Hemoglobin levels increased from 10.6 to 11g/dl with little improvement ( p ≤ 0.05) in proteins, albumin and other indices of blood profile and nine subjects fell in non-anemic category. Research limitations/implications: The diets of both groups were not controlled, which might have varied the results. Practical implications: Garden cress-seed-enriched biscuits were able to have a positive impact on the nutritional profile of malnourished and anemic school children. Social/implications: The duration of supplementation was short, which may have affected these results. Therefore, researchers are encouraged to perform long-duration supplementation study for more accurate results. Originality/value: This paper identifies the need for promoting garden cress seeds in supplementary foods to reduce malnutrition.